Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages ERRATA. The author of this pamphlet was prevented by illness from correcting the proofs, and apologises to readers for the following errors and omissions :— Page 4. For Per capital read per capita. Page 5. In table of upper class education, for 6 years at £120 read 5 years at £120. For 5 years at £180 read 4 years at £180. Page 6. Line 6. Omit the word in. Line 10. Omit the words Nearly all the remainder. Page 17. The numbers of unemployed (i.e., those registered with the Ministry of Labour) are given in thousands. Page 17. Since November, 1944, new rates are in force. A single man now gets 24/- and a single woman 22/-. 5/- is paid for each of the first two children and 4/- for each subsequent child. The allowance for a dependent adult is 16/-. Thus the allowance for a family of 4 is now 50/-. Page 18. Line 24. For a diet adequate for health could be read a diet adequate for health could not be. The Assistance Board's scales are now as follows:— Unemployment Assistance. Supplementary Pensions. If the applicant is a householder: Husband and wife 31/- 35/- Single householder 18/- 20/- Child under 8 6/- „ 8/11 7/6 „ 11/16 9/- Dependants : 16-21 12/6 „ Over 21 15/- A separate allowance is now made for rent, equal to the rent actually paid by the applicant, so far as is reasonable. Page 18. Line 36. The next table, showing contributions required from non-dependent members of an assisted household, should read as follows:— From a wage of 55/- and over Contribution 7/- „ „ „ 30/- to 55/- „ 5/- „ „ „ 20/- to 30/- „ 2/6 „ „ „ below 20/- „ Nil Page 20. Omit lines 1-3 which are out of date. See Assistance Board's scales above. 15X/2/98/13